PREVALENCE OF CONTACT LENS RELATED DRY EYE (CLRDE) AMONG CONTACT LENS WEARER IN MALAYSIA - MOHAMAD DAUD, SYAHIRAH AMERAH; BADARUDIN, NOOR EZAILINA (International Journal of Allied Health Sciences, 2020)
Objective: To determine the prevalence of contact lens related dry eyes among contact lens wearer in Malaysia, to identify the association between age and the dry eye symptoms and to study the association between duration of contact lens wear and the dry eye symptoms. Materials and methods: An online survey of Contact Lens Dry Eye Questionnaire (CLDEQ-8) was distributed through media socials. Information on participantsâ€™ age, gender, type of contact lens wear, and duration of wearing contact lens were included. Results: A total of 140 contact lens wearer completed the online survey with 94.3% of female participants. The type of contact lens used by the participants were mostly soft contact lens (98.6%) with monthly disposable modality (75.0%) followed by daily disposable modality (15.7%). Most of the participants reported eye discomfort â€œsometimesâ€ (48.6%) for the last 2 weeks with the intensity level of discomfort on scale â€œ3â€ (31.4%), followed by dryness â€œsometimesâ€ (39.3%) with intensity of â€œ2â€ (29.3%) at the end of the wearing time. There are significant correlation between age and the dry eyes symptoms which are the frequency of eyes discomfort and having to remove lenses (p < 0.05). However, there is no association between the duration of contact lens wear and the dry eyes symptoms (p > 0.05). Conclusion: Eye dryness is the most reported symptom which is more frequent and intense at the end of wearing time.